A quad-cliff mechanism for eco-printing by pounding technique: design, manufacturing, and testing - Triawan, Farid; Dyota, Arya Smara; Kamila, Fatima Tasya; Saptaji, Kushendarsyah; Fernandez, Nikolas Krisma Hadi; Silitonga, Arridina Susan; Sebayang, Abdi Hanra (Jurnal Polimesin, 2024)
Indonesia produces many types of textile products, such as clothing and custom fabrics often with unique patterns. To generate the patterns, there are many methods, including eco-printing by pounding process. However, the process, which was later referred to as eco-pounding, requires much time and energy, which can have a negative impact, such as musculoskeletal disorders, on the human body. To address this issue, the present work proposes a machine that can help the process of eco-pounding. Shigley’s method is applied to guide the design process of the machine. The design and manufacturing processes of the eco-pounding machine are presented, in which three machine design models are first introduced and then analyzed for finalization by benchmarking method. Subsequently, a machine model that uses a so-called quad-cliff mechanism is selected for manufacturing and testing. As a result, the proposed machine can achieve the design requirements that were set. Three pounding movements per second can be obtained by the machine, with possible increases by an engine upgrade. This machine can be considered a prototype for a semi-automatic eco-printing process by pounding technique.